ANALYSIS OF STUDENT ERRORS IN SOLVING THE SYSTEMS OF INEQUALITIES WITH TWO VARIABLES PROBLEMS BASED ON NEWMAN - Resi Erni (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2021)
Mathematics is a field of education that can provide recommendations in our daily lives. Mathematics can help us to think logically, critically, and creatively. The stages of error analysis that are appropriate and that can be carried out in the form of Two Variable Inequality System questions are the stages of error analysis according to Newman (NEA). Newman (Clemen, 1980) suggests that if students want to solve math problems in the form of story problems through five steps, namely asking students to: (1) read the questions (reading), (2) understand the problem (comprehension), (3) transformation, (4) process skills, and (5) writing final answer (encoding). This research was conducted at SMA Negeri 1 Hulu Kuantan in the odd semester of the 2020/2021 school year. The sample of this study were 25 students of class XII MIPA 1. This research was conducted on Thursday, November 26, 2020. The research method is descriptive research. Based on the analysis conducted, it was found that the percentage of students' errors was 21.6% of errors in question number 1, the error in number 2 was 35.7%, the error in number 3 was 48%, the error in number 4 was 26.7%. From the data processing, it was found that the most student errors occurred in question number 3. The percentage of reading error was 36%, comprehension error was 72%, transformation error was 56%, process skill error was 64%, and Encording Error was 52%.